Development of Aircraft Movement Simulation in Airport Airside Area - M Sadono; D Y Putra; S A Harahap (AVIA, 2020)
Soekarno-Hatta Intl Airport had become busier every and each year passed. Based on Airnav’s data in 2016, there was about 1.200 aircraft movement, included take-off and landing, happened in Soekarno-Hatta Intl Airport in one day. These numerous movements made Soekarno-Hatta Intl Airport became the 12th busiest airport in the world based on Airport Council International (ACI). The long queue of the aircraft at the taxiway is deniable and became one of the problems that needs to be resolved. This research would make aircrafts movement simulation in Soekarno-Hatta Intl Airport’s taxiway(s) using Rockwell Arena Simulation software. The simulation results would be total taxiing time of an aircraft, which intersection(s) that traffic happened, and the total of aircraft(s) that doing taxi in and taxi out. This simulation would help to determine and evaluate the factors that initiated the queue in the taxiway and modify taxiing route to reduce the traffic. The results of this research can be applied by the airport as a reference for scheduling aircraft’s departing or arriving, develop airport airside facility, and to improve taxiing route so the duration of aircraft’s taxiing time can be reduced